Nitrogen Removal and N2O Emission in Biochar‐Sludge Subsurface Wastewater Infiltration Systems. (1st September 2018) - Qi, Shiyue; Zhao, Yue; Wang, Shiyao; Zheng, Fanping; Pan, Jing; Fan, Linlin; Li, Zhiqi; Tan, Chaoquan; Hou, Wanyuan
Abstract : Nitrogen removal and N2 O emission of biochar‐sludge amended subsurface wastewater infiltration systems (SWISs) with/without intermittent aeration under different organic surface loading rates (OSLRs) were investigated. Under OSLR, between 8.5 and 54.6 g COD/(m 2 d), average chemical oxygen demand (COD), NH + 4 ‐N, and total nitrogen (TN) removal rates decreased with OSLR increasing in non‐aerated SWISs amended with/without biochar‐sludge; increasing OSLR hardly affected COD and NH + 4 ‐N, removal in biochar‐sludge amended SWIS with intermittent aeration; N2 O emission rate decreased with influent OSLR increasing in the SWISs. Biochar‐sludge amended SWIS with intermittent aeration obtained higher removal rates for COD (94.9 to 95.5%), NH + 4 ‐N, (90.5 to 93.7%), TN (86.5 to 89.9%) and lower N2 O emission rates [13.4 to 14.7 mg/(m 2 d)] under high influent OSLR of 36.2 and 54.6 g COD/(m 2 d) were compared with non‐aerated SWISs with/without biochar‐sludge. Furthermore, the abundances of amoA, nxrA, napA, narG, nirS, nirK, qnorB, and nosZ genes involved in nitrogen removal were enhanced under high influent OSLR in biochar‐sludge amended SWIS with intermittent aeration.